Vitamin D Deficiency among Children Visiting Outpatient Department in Bangladesh Shishu Hospital & Institute (The Insight, 2025)
Background: Vitamin D plays a crucial role in bone mineralization, immune function, and overall growth. Deficiency is a widespread public health concern, particularly among children in South Asia, including Bangladesh. Limited sun exposure and dietary insufficiency are recognized contributors, but the prevalence and associated risk factors remain underreported in pediatric outpatient populations. Aim of the study: To determine the prevalence, risk factors, and clinical impact of vitamin D deficiency among children attending outpatient departments of Bangladesh Shishu Hospital & Institute. Methods & Martials: A cross-sectional study was conducted from From January 2024 to December 2024 on 210 pediatric patients (
Keywords: Vitamin D deficiency; Pediatric; Sunlight exposure; Bangladesh; 25-hydroxyvitamin D